2012
DOI: 10.1021/jo202607z
|View full text |Cite
|
Sign up to set email alerts
|

Bi(III)-Catalyzed Intermolecular Reactions of (Z)-Pent-2-en-4-yl Acetates with Ethynylarenes for the Construction of Multisubstituted Fluorene Skeletons through a Cascade Electrophilic Addition/Cycloisomerization Sequence

Abstract: A Bi(III)-catalyzed method for the synthesis of highly conjugated aromatic multisubstituted fluorene with (Z)-pent-2-en-4-yl acetates and ethynylarenes via domino reaction is described. In this process, the reaction appears to be very general and suitable for a variety of multisubstituted fluorene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…( Z )-Pent-2-en-4-yl acetates react with ethynylarenes (MeNO 2 , 80 °C, 6–12 h) in the presence of Bi­(III) (BiBr 3 10 mol %, 2,2′-bipyridine 20 mol %) to obtain substituted fluorenes (18 examples, 51–82%) …”
Section: Reactions Catalyzed By Other Metalsmentioning
confidence: 99%
“…( Z )-Pent-2-en-4-yl acetates react with ethynylarenes (MeNO 2 , 80 °C, 6–12 h) in the presence of Bi­(III) (BiBr 3 10 mol %, 2,2′-bipyridine 20 mol %) to obtain substituted fluorenes (18 examples, 51–82%) …”
Section: Reactions Catalyzed By Other Metalsmentioning
confidence: 99%
“…A recent Bi III ‐catalyzed synthesis of multisubstituted fluorenes was reported by Liang and co‐workers, who found that the reaction of ( Z )‐pent‐2‐en‐4‐yl acetates 50 with ethynylarenes 51 in the presence of BiBr 3 (10 mol %) and 2,2′‐bipyridine (20 mol %) in CH 3 NO 2 afforded fluorene derivatives 52 in moderate to good yields (Scheme ) 37. Based on the experimental observations, a mechanistic rationale was proposed (Scheme ).…”
Section: Other Transition Metal‐catalyzed Syntheses Of Fluorenesmentioning
confidence: 99%
“…The scope of the cyclization towards the various fluorenes and fluorenols was investigated and the reaction proved to be general for various substrates. For other methods of synthesis of the fluorene core, see the references [16–19] . We noticed an instability of some synthesized products which upon standing changed color to purple/red.…”
Section: Introductionmentioning
confidence: 87%